2004
DOI: 10.1080/13668250412331285127
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Stones Triple P: the theoretical basis and development of an evidence‐based positive parenting program for families with a child who has a disability

Abstract: Stepping Stones Triple P (SSTP) is the first in a series of programs based on the Triple P -Positive Parenting Program that has been specifically designed for families who have a child with a disability. This paper presents the rationale, theoretical foundations, historical development and distinguishing features of the program. The multi-level intervention adopts a self-regulation framework in consulting with parents that involves the promotion of parental self-sufficiency, self-efficacy, self-management skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 26 publications
0
103
0
9
Order By: Relevance
“…Das in Australien entwickelte präventive Elterntrainingsprogramm Stepping Stones Triple P (SSTP) (Sanders, Mazzucchelli, Studman, 2004a) für Eltern behinderter Kinder wird derzeit auch im deutschsprachigen Raum erprobt. In der vorliegenden Studie wird ein Überblick über den aktuellen Forschungsstand zur Validität des SSTP gegeben.…”
Section: Zusammenfassungunclassified
See 2 more Smart Citations
“…Das in Australien entwickelte präventive Elterntrainingsprogramm Stepping Stones Triple P (SSTP) (Sanders, Mazzucchelli, Studman, 2004a) für Eltern behinderter Kinder wird derzeit auch im deutschsprachigen Raum erprobt. In der vorliegenden Studie wird ein Überblick über den aktuellen Forschungsstand zur Validität des SSTP gegeben.…”
Section: Zusammenfassungunclassified
“…Das Programm SSTP (deutsche Bearbeitung: Sanders et al, 2004b) gehört zur "Triple-P-Familie". Es wurde aus dem Standard-Triple P-Programm (Überblick: Kuschel, Beslmei-sel, Hahlweg, Hautzinger, 2007), abgeleitet, dem es in Zielen und Aubau ähnelt (Sanders et al, 2004a;Probst u. Spreitz, 2008). Die wesentlichen Programm-Materialien bestehen aus dem "SSTP: Begleitbuch zum Elterngruppentraining" (Sanders et al, 2004b) und Video "SSTP: Überlebenshilfe für Eltern von Kindern mit einer Behinderung" (Sanders et al, 2005).…”
Section: Präventives Elternprogramm Stepping Stones Triple P: Ziele Uunclassified
See 1 more Smart Citation
“…It is a matter of concern to teachers and parents when children display maladjusted behaviours, particularly when they present atypical development. During the last two decades, several parental programmes have been developed in order to support social adjustment in typically developing (TD) children (e.g., Havighurst, Wilson, Harley, & Prior, 2009) and children with atypical development (e.g., Herbert, Harvey, Roberts, Wichowski, & Lugo-Candelas, 2013;Sanders, Mazzucchelli, & Studman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Incredible Years program (Webster-Stratton, 2001) has been adapted and piloted with parents of children with developmental delay (McIntyre, 2008). Triple P (Sanders, 1999) has been adapted to be used with parents whose children have various disabilities and is known as Stepping Stones Triple P (SSTP; Sanders et al, 2004); SSTP has been evaluated in several RCTs and a recent meta-analysis summarized available evidence from nine RCTs and three uncontrolled studies (Tellegen and Sanders, 2013). Findings indicated that immediately after SSTP, there were significant improvements in child problem behaviors and improvements in parenting skills among parents of children with various developmental disabilities.…”
mentioning
confidence: 99%